KREATIVITAS MUSIK GAMBANG SEMARANG STUDI KASUS KOMUNITAS GAMBANG SEMARANG ART COMPANY - Ricky Alfiantoro (SELONDING, 2017)
Gambang Semarang is one of the original art Gambang Semarang are adopting Kromong Betawi arts. Gambang Semarang was born in 1930 on the initiative of Lie Soen Hoo who is a member Volkstraad (House of Representatives during the reign of the Netherlands). At present Gambang Semarang has created a form that has a factor in creativity. Creativity is an aspect of human qualities which currently play an important role in supporting the development of the nation Indonesian who are experiencing problems are complex, because creativity will have the ability, the creative adaptation and expertise imaginative, so that people will be able to find a resolution problems in a new way in follow the changes that occur that will continue to move towards progress for not float and sink in competition between nations and countries, especially in this era of globalization.               Gambang Semarang Art Company is a community of young people who are active in preserving the arts Gambang Semarang with attractive feature, which will follow the tastes of the market in contemporary times, a rendition of the popular and also add some western instruments in the ensemble. Their communities Gambang Semarang Art Company is very important to introduce art Gambang Semarang are increasingly recognized by the people of Semarang.               Research Gambang Semarang Art Company uses the description of the analysis method with the approach of ethnomusicology. The results obtained in these studies is a form of imitation of Gambang Semarang are packed in Gambang Semarang Art Company can produce and the continued existence of Gambang Semarang as regional identity. Keywords: Gambang Semarang, Creativity, Community Gambang Semarang Art Company.